Penerapan Metode Overview, Key Ideas, Read, Record, Recite, Review dan Reflect untuk Meningkatkan Kemampuan Membaca Pemahaman Siswa Sekolah Dasar - Ina Yati; Herlina Herlina; Syarifuddin - (el-Ibtidaiy:Journal of Primary Education, 2021)
This study aims to determine the improvement of elementary school students' reading comprehension skills through the application of overview, key ideas, read, record, recite, review and reflect methods. This research is motivated by the lack of students' ability to understand the reading text that is read. This research is a classroom action research. Data collection techniques in this study were observation, students' reading comprehension test and documentation. While the data analysis technique used is a qualitative descriptive analysis technique with a percentage. Based on research and data analysis that the application of overview, key ideas, read, record, recite, review and reflect methods can improve students' reading comprehension skills. This can be seen from the test results of students' reading comprehension before the action only reached an average of 58.42 with classical completeness of 42.85% or classified as poor. After applying the overview, key ideas, read, record, recite, review and reflect methods in the first cycle, the students' reading comprehension ability increased by an average of 72.28 with a classical completeness of 66.66% or quite good. In the second cycle, the results of students' reading comprehension increased by an average of 81.23 with classical completeness of 85.71% or classified as good. Thus it can be concluded that the overview, key ideas, read, record, recite, review and reflect methods can improve the reading comprehension ability of elementary school students.